A mixed-linkage (1, 3;1, 4)-β-D-glucan specific hydrolase mediates dark-triggered degradation of this plant cell wall polysaccharide. Issue 4 (28th January 2021) - Kraemer, Florian J; Lunde, China; Koch, Moritz; Kuhn, Benjamin M; Ruehl, Clemens; Brown, Patrick J; Hoffmann, Philipp; Göhre, Vera; Hake, Sarah; Pauly, Markus; Ramírez, Vicente
Abstract: The presence of mixed-linkage (1, 3;1, 4)-β-d -glucan (MLG) in plant cell walls is a key feature of grass species such as cereals, the main source of calorie intake for humans and cattle. Accumulation of this polysaccharide involves the coordinated regulation of biosynthetic and metabolic machineries. While several components of the MLG biosynthesis machinery have been identified in diverse plant species, degradation of MLG is poorly understood. In this study, we performed a large-scale forward genetic screen for maize ( Zea mays ) mutants with altered cell wall polysaccharide structural properties. As a result, we identified a maize mutant with increased MLG content in several tissues, including adult leaves and senesced organs, where only trace amounts of MLG are usually detected. The causative mutation was found in the GRMZM2G137535 gene, encoding a GH17 licheninase as demonstrated by an in vitro activity assay of the heterologously expressed protein. In addition, maize plants overexpressing GRMZM2G137535 exhibit a 90% reduction in MLG content, indicating that the protein is not only required, but its expression is sufficient to degrade MLG. Accordingly, the mutant was named MLG hydrolase 1 ( mlgh1 ). mlgh1 plants show increased saccharification yields upon enzymatic digestion. Stacking mlgh1 with lignin-deficient mutations results in synergistic increases in saccharification. Time profiling experiments indicate that wall MLG content is modulated during day/night cycles, inversely associated with MLGH1 transcript accumulation. This cycling is absent in the mlgh1 mutant, suggesting that the mechanism involved requires MLG degradation, which may in turn regulate MLGH1 gene expression. Abstract : Dark-induced degradation of the grass cell wall polysaccharide mixed-linkage glucan (MLG) is mediated by MLG HYDROLASE 1.